2016
DOI: 10.1007/s11357-015-9863-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes and interactions of autonomic functioning and sleep architecture before and after 50 years of age

Abstract: We hypothesize that the time when age-related changes in autonomic functioning and in sleep structure occur are different and that autonomic functioning modulates sleep architecture differently before and after 50 years of age. Sixty-eight healthy subjects (aged 20 to 79 years old, 49 of them women) were enrolled. Correlation analysis revealed that wake after sleep onset, the absolute and relative value of stage 1 (S1; S1%), and relative value of stage 2 (S2) were positively correlated with age; however, sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 55 publications
5
11
0
2
Order By: Relevance
“…The decrease of heart rate with age has been confirmed by several studies in the literature (O'Brien et al, 1986;Larson et al, 2013;Porta et al, 2014). Similar findings are reported in a recent study by Kuo et al (2016). The authors (Kuo et al, 2016) investigated changes and interactions of autonomic functioning with age and sleep architecture and found that ANS has different effects on sleep FIGURE 5 | (Left) LFnu 10 min before sleep onset between short and long SOL for all age groups as measured by GLM model, χ 2 = 2.76, p = 0.09.…”
Section: Figure 3 | (Left)supporting
confidence: 88%
See 1 more Smart Citation
“…The decrease of heart rate with age has been confirmed by several studies in the literature (O'Brien et al, 1986;Larson et al, 2013;Porta et al, 2014). Similar findings are reported in a recent study by Kuo et al (2016). The authors (Kuo et al, 2016) investigated changes and interactions of autonomic functioning with age and sleep architecture and found that ANS has different effects on sleep FIGURE 5 | (Left) LFnu 10 min before sleep onset between short and long SOL for all age groups as measured by GLM model, χ 2 = 2.76, p = 0.09.…”
Section: Figure 3 | (Left)supporting
confidence: 88%
“…Similar findings are reported in a recent study by Kuo et al (2016). The authors (Kuo et al, 2016) investigated changes and interactions of autonomic functioning with age and sleep architecture and found that ANS has different effects on sleep FIGURE 5 | (Left) LFnu 10 min before sleep onset between short and long SOL for all age groups as measured by GLM model, χ 2 = 2.76, p = 0.09. (Right) HFnu 10 min before sleep onset between short and long SOL for all age groups as measured by GLM model, χ 2 = 3.88, p < 0.05. n, number of participants in the SOL group for the specific age group (bold for the long SOL group).…”
Section: Figure 3 | (Left)supporting
confidence: 83%
“…Paralelamente, há diminuição do tempo total e da qualidade do sono 5 , pois os idosos também atenuam os níveis R. bras. Ci.…”
Section: Discussionunclassified
“…A insônia é considerada um distúrbio predominante em idosos 3 . Os mecanismos subjacentes envolvidos pela elevada taxa de incidência de distúrbio de sono na população idosa pode ser explicado pela regressão da fisiologia do sono em consonância com progressão etária, prevalência da apneia do sono e multimorbilidades [4][5][6] .…”
Section: Introductionunclassified
“…Oxygen availability, being restored along descent, leads, indeed, to a rebound of parasympathetic tonus [254]. Vagotonusinversely relates to age [255,256] and tends to be augmented by melatonin [257][258][259]. Enhanced vagal activity can lead to accidents by provoking failures in consciousness.…”
Section: Death In the Mountainmentioning
confidence: 99%